Deixis Analysis in the Song Lyrics of Ed Sheeranâs `Divide` Album - Nasution, Deby Rizka Afrilia; Setiadi, Gunawan; Ilza, Shena Samira (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research aims to analyze five types of deixis by using theory of Alan Cruse (2000), interpret the reference meaning of deixis and find out the most dominant type of deixis that found in the song lyrics of Ed Sheeranâs album. The researcher elects Divide album as the object of the analysis because it is one of the best-selling album in the world. it consists of such deictic words that has reference meanings. Therefore, the song lyrics can be analyzed using pragmatic approach, specifically about deixis. This study was conducted by using descriptive qualitative method. The data which is used is six songs of Ed Sheeranâs album and then they are classified into the types of deixis based on their own criteria. The findings showed that the types of deixis like person deixis, spatial deixis, temporal deixis, social deixis and discourse deixis are used in the song lyrics of Ed Sheeranâs Album. Based on discussion and finding can be concluded that all deixis are found in all songs, personal deixis is the most being found (46 Deictic words or 28%) the word âI. Me, My, You and Your dominate all songs. in the second position Temporal Deixis is the most being found (43 deictic words or 26%) the word now dominate in all songs. the third position is Spatial deixis (41 Deictic words or 25% ) in the fourth position is Discourse Deixis (20 deictic words or 12%) and in the last position is Social Deixis (15 Deictic words or 9%).